2005
DOI: 10.1007/s00359-005-0059-4
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory neural control of posterograde heartbeat by the frontal ganglion in the last instar larva of a lepidopteran, Bombyx mori

Abstract: The frontal ganglion of the silkworm (Bombyx mori) gives rise to a visceral nerve, branches of which include a pair of anterior cardiac nerves and a pair of the posterior cardiac nerves. Forward-fill of the visceral nerve with dextran labeled with tetramethyl rhodamine shows the anterior cardiac nerves innervate the anterior region of the dorsal vessel. Back-fill of the anterior cardiac nerves with Co(2+) and Ni(2+) ions and the fluorescent dye reveals that the cell bodies of two motor neurons are located in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…All mea-Vo Vco 2 2 surements were made ∼12 h after feeding to minimize variability in resulting from specific dynamic action. Hormonal Vo 2 activity has been linked to the light-dark cycle in silkworms (Fugo et al 1984), and changes in light and/or dark have also been shown to alter and heart rate and/or cause heart ratė Vo 2 reversals in other insect species (Stusek et al 2000;Uchimura et al 2005). Therefore, all of the incubators, holding chambers, and respirometers were transparent to admit ambient light, and all measurements were made during daylight hours to control for normal circadian rhythms.…”
Section: Respirometrymentioning
confidence: 99%
“…All mea-Vo Vco 2 2 surements were made ∼12 h after feeding to minimize variability in resulting from specific dynamic action. Hormonal Vo 2 activity has been linked to the light-dark cycle in silkworms (Fugo et al 1984), and changes in light and/or dark have also been shown to alter and heart rate and/or cause heart ratė Vo 2 reversals in other insect species (Stusek et al 2000;Uchimura et al 2005). Therefore, all of the incubators, holding chambers, and respirometers were transparent to admit ambient light, and all measurements were made during daylight hours to control for normal circadian rhythms.…”
Section: Respirometrymentioning
confidence: 99%